2003
DOI: 10.1124/jpet.102.042077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nepadutant, a Neurokinin 2 Tachykinin Receptor Antagonist, on Immediate-Early Gene Expression after Trinitrobenzenesulfonic Acid-Induced Colitis in the Rat

Abstract: Tachykinins have been implicated in inflammatory responses such as those occurring in inflammatory bowel disease. Accordingly, we investigated the effect of a selective neurokinin (NK) 2 receptor antagonist, nepadutant, on proto-oncogene expression in the L 6 -S 1 spinal cord as well as in dorsal root ganglion (DRG) neurons after either non-noxious colorectal distension (CRD) or trinitrobenzenesulfonic acid (TNBS)-induced colitis in the adult rat. In both preparations, c-fos was expressed in similar spinal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…For the same reasons, many compounds designed for human neurokinin receptors failed to exhibit any analgesic effect in animal studies. Regardless, several animal studies have documented that selective antagonists for all three receptors (NK1, NK2, and NK3) attenuate visceral pain in several animal species, including mice, rats, rabbits, guinea pigs and gerbils (Gardeau and Plourde 2003; Julia et al 1994, 1999; Laird et al 2001a, b; Kamp et al 2001; Fioramonti et al 2003; Birder et al 2003; Greenwood-van Meerveld et al 2003; Bradesi et al 2003; Okano et al 2002; Kakol-Palm et al 2008). Although in many of these studies, the sites of action of the antagonists were not well characterized, presumably most of the antagonists modulate spinal processing by blocking presynaptic and/or postsynaptic neurokinin receptors in the spinal cord.…”
Section: Contribution Of Sensory Afferents In Visceral Painmentioning
confidence: 99%
See 1 more Smart Citation
“…For the same reasons, many compounds designed for human neurokinin receptors failed to exhibit any analgesic effect in animal studies. Regardless, several animal studies have documented that selective antagonists for all three receptors (NK1, NK2, and NK3) attenuate visceral pain in several animal species, including mice, rats, rabbits, guinea pigs and gerbils (Gardeau and Plourde 2003; Julia et al 1994, 1999; Laird et al 2001a, b; Kamp et al 2001; Fioramonti et al 2003; Birder et al 2003; Greenwood-van Meerveld et al 2003; Bradesi et al 2003; Okano et al 2002; Kakol-Palm et al 2008). Although in many of these studies, the sites of action of the antagonists were not well characterized, presumably most of the antagonists modulate spinal processing by blocking presynaptic and/or postsynaptic neurokinin receptors in the spinal cord.…”
Section: Contribution Of Sensory Afferents In Visceral Painmentioning
confidence: 99%
“…Similarly, there are a few reports of the evaluation of the peripheral effects of these drugs. Two reports have documented the inhibitory effects of NK2 and NK3 receptor antagonists on colonic PN afferents (Julia et al 1999; Birder et al 2003). …”
Section: Contribution Of Sensory Afferents In Visceral Painmentioning
confidence: 99%
“…(16) Immediateearly genes (such as c-fos) have been reported to be elevated in the lumbosacral spinal cord and DRG following bladder and colon irritation. (17)(18)(19) NGF, a potent mediator of hyperalgesia associated with inflammation, is upregulated in response to LPS in a mouse cystitis model. (20) We also examined changes in MIF and COX-2 in the prostate in a preliminary attempt to study the possible role of MIF in viscerovisceral interactions.…”
Section: Introduction B Ladder Inflammation Is Associated With Urinarmentioning
confidence: 99%
“…However the increase in myenteric and mucosal tachykinins substance P (SP) and neuropeptide K (NPK) persisted for at least 14 weeks as did the increase in circular muscle thickness. These studies suggested that mucosal tachykinins and galanin might be good mucosal markers of both previous postinflammatory neural damage and persistent increase in myenteric tachykinins, which might in turn relate to visceral hypersensitivity as recent animal studies have suggested 16–18 …”
Section: Introductionmentioning
confidence: 99%